A core outcome set for trials of infant-feeding interventions to prevent childhood obesity - Hayes, Catherine (My University, 2020)
Standardisation of outcomes measured and reported in trials of infant-feeding interventions to prevent childhood obesity is essential to evaluate and synthesise intervention effects. The aim of this study is to develop an infant feeding core outcome set for use in randomised trials of infant feeding interventions to prevent childhood obesity. Core outcome set development followed four stages: 1) systematic review of outcomes reported in the extant literature; 2) meeting with national and international stakeholders to discuss and clarify identified outcomes; 3) e-Delphi study with national and international stakeholders to prioritise outcomes; 4) meeting with national and international stakeholders to reach consensus on outcomes. Stakeholders in stages 2- 4 were paediatricians, general practitioners, nurses, midwives, non-clinician researchers, parents, dieticians, nutritionists, and childcare providers. Twenty-six outcomes were identified for inclusion in the core outcome set. These were grouped in nine outcome domains: ‘breastfeeding and formula feeding’, ‘introduction of solids’, ‘parent feeding practices and styles’, ‘parent knowledge and beliefs’, ‘practical feeding’, ‘food environment’, ‘dietary intake’, ‘perceptions of infant behaviour and preferences’, and ‘child weight’. The core outcome set identified in this study is the minimum that should be measured and reported in trials of infant-feeding interventions to prevent childhood obesity. This standardisation of outcomes will enable more comprehensive examination and synthesis of the effects of infant feeding interventions to prevent childhood obesity.
PUBLISHED